2020
DOI: 10.1007/s10555-020-09869-8
|View full text |Cite
|
Sign up to set email alerts
|

How progressive cancer endangers the heart: an intriguing and underestimated problem

Abstract: Since it came into being as a discipline, cardio-oncology has focused on the prevention and treatment of cardiotoxicity induced by antitumor chemotherapy and radiotherapy. Over time, it has been proved that even more detrimental is the direct effect generated by cancer cells that release pro-cachectic factors in the bloodstream. Secreted molecules target different organs at a distance, including the heart. Inflammatory and neuronal modulators released by the tumor bulk, either as free molecules or through exos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 164 publications
2
17
0
Order By: Relevance
“…[3][4][5][6] Further, given the severe metabolic dysregulation and hypercatabolism that persists with cachexia, it is no surprise that clinical and experimental investigations have identified perturbations in several tissues besides skeletal muscle, including fat, bone, and heart. 3,[7][8][9][10] Unfortunately, viable treatment options to counteract cachexia, especially in the most advanced stages of cancer, remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Further, given the severe metabolic dysregulation and hypercatabolism that persists with cachexia, it is no surprise that clinical and experimental investigations have identified perturbations in several tissues besides skeletal muscle, including fat, bone, and heart. 3,[7][8][9][10] Unfortunately, viable treatment options to counteract cachexia, especially in the most advanced stages of cancer, remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, muscle wasting is not an exclusive feature of skeletal muscle involved in locomotion, it has also been shown to affect respiratory muscles and even myocardium in patients with chronic disease-associated wasting [36][37][38]. Additionally, the progression of tumor cells, as well as cardiotoxicity induced by cancer treatment, may lead to a condition called "cardiac cachexia" that is characterized by cardiac atrophy, fibrosis, and myocardial dysfunction [39].…”
Section: Altered Energy Balancementioning
confidence: 99%
“…Clinical and experimental studies have demonstrated that cancer patients develop cardiac disease not only as a consequence of cardiotoxicity induced by chemotherapies, but also because tumor cells release soluble factors that affect various organs at a distance, including the heart (1, 2). Cancer-derived pro-inflammatory molecules cause cardiomyocyte atrophy and tissue remodeling, which can degenerate to cachexia and HF (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%